AN ANALYSIS OF THE PIANO SONATA IN C MINOR, OP. 4 BY FRÉDÉRIC CHOPIN - FRĂŢILĂ, Lioara (Studia Universitatis Babes-Bolyai Musica, 2021)
The aura of the composer Frédéric Chopin penetrated the Western European musical culture, touching massively other cultures as well, up to the Chinese one; the certainty through which we recognize the thrill of this aura is mostly due to the fact that ”Chopin’s compositions have opened a new era in the piano’s history” . Being present in the Parisian salon with Rossini and Liszt, the great Pole achieved an organic interweaving between the tradition of Austro-German and French music. The analysis of the sonata No. 1 in C-minor op. 4 builds the core of the present study and relevantly denotes the connection of its architecture together with the set of conventions belonging to the format of the sonata-genre coming from Beethoven. As we know, the Sonata-pattern designed by Beethoven was expanded throughout the Romantic period as well as the conditions under which the aesthetics of Romanticism found a specific corridor reaching its maximum of expression. In a way of an idiomatic, natural model of transmission, the Chopin’s style of conceiving music played its predominant role. Taking into account in this approach theories belonging to the aesthetics field and some theoretical applications with significance for understanding the levers of construction concerning this sonata, op. 4 (composed when the composer was only eighteen (1828)) and Chopin’s approach of the other stages of emancipation within the genre, I will highlight its rules which emphasize implicitly the dialogue with the ”Sonata-Fantasy” genre, as this construct appears (for instance) in sonata op. 58. Rezumat. O ANALIZĂ A SONATEI PENTRU PIAN ÎN DO MINOR, OP. 4 DE FRÉDÉRIC CHOPIN. Aura compozitorului Frédéric Chopin a pătruns în cultura muzicală vest-europeană, atingând masiv și alte culturi, până la cea chineză; certitudinea prin care recunoaștem fiorul acestei aurE se datorează în principal faptului că „compozițiile lui Chopin au deschis o nouă eră în istoria pianului”. Fiind prezent în salonul parizian cu Rossini și Liszt, marele polonez a realizat o legătură organică între tradiția muzicii austro-germane și franceze. Analiza sonatei nr. 1 în do minor op. 4 construiește nucleul prezentului studiu și denotă în mod relevant conexiunea arhitecturii sale împreună cu setul de convenții aparținând formatului genului sonatei provenind de la Beethoven. După cum știm, modelul Sonatei structurat de Beethoven a fost extins de-a lungul perioadei romantice, precum și condițiile în care estetica romantismului a găsit un coridor specific atingând culmea sa expresivă. Într-un mod de transmisie idiomatică, naturală, stilul lui Chopin de a concepe muzica și-a jucat rolul predominant. Luând în considerare în această abordare teoriile aparținând domeniului estetic și câteva aplicații teoretice cu semnificație pentru înțelegerea nivelurilor de construcție referitoare la această sonată, op. 4 (compusă când compozitorul avea doar optsprezece ani (1828)) și abordarea de către Chopin a celorlalte etape de emancipare din cadrul genului, voi sublinia regulile sale în dialog implicit cu genul „Sonatei-Fantasy”, pe măsură ce apare această construcție (de exemplu) în sonata op. 58. Cuvinte cheie: limbaj, sonata bitematică, polifonie, formă, evoluție